Answers

2014-06-21T23:15:14+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
X+y=3.3 => x=3.3-y now put this value of x in equ 2 we get 0.6 { 3(3.3-y)-2y}-2y=-1 => 0.6{ 9.9y -2y } -2y =-1 => 0.6*7.9y -2y =-1 =>4.74y-2y=-1 => 2.74y=-1=> y= 1/2.74 = 0.364 now x=3.3 -y => 3.3 - 0.364 = 2.935 answer
1 1 1
  • Brainly User
2014-06-22T22:02:53+05:30
The answer will be
2.935
hope this helps

1 1 1